Anaerobic digestion of crude glycerol: a review - Viana, Michael Barbosa (2012)
Several researchers have used crude glycerol as a source of substrate for methane production and power generation, which is a way of adding value to this residue that has a high chemical oxygen demand (COD) and is rich in impurities. This review article summarizes recent data and discussions on the use of crude glycerol as substrate and co-substrate for anaerobic digestion. In general, the dilution of glycerol has been used to avoid problems of inhibition due to the presence of inorganic salts of chloride and sulphates, and due to accumulation of metabolites. However, other methods have been proposed, such as the use of halo-tolerant biomass. It can be concluded that the anaerobic digestion of crude glycerol is technically viable, and an anaerobic reactor treating 25 m3 per day .